2018
DOI: 10.1186/s13613-018-0441-3
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative statin therapy in cardiac and non-cardiac surgery: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundThe effects of perioperative statin therapy on clinical outcome after cardiac or non-cardiac surgery are controversial. We aimed to assess the association between perioperative statin therapy and postoperative outcome.MethodsElectronic databases were searched up to May 1, 2018, for randomized controlled trials of perioperative statin therapy versus placebo or no treatment in adult cardiac or non-cardiac surgery. Postoperative outcomes were: myocardial infarction, stroke, acute kidney injury (AKI), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 48 publications
3
32
0
8
Order By: Relevance
“…Preoperative statin therapy was not associated with a significantly different time to reach the peak during iontophoresis of ACh. This result is consistent with previous studies that found neutral or detrimental effects of statins in cardiac surgery particularly about the kidney outcomes [ 36 ]. In the same way, despite the detrimental effect of atrial fibrillation, a chronic beta-blocker therapy was not associated with a decrease in organ dysfunction or a shorter time to reach the peak during iontophoresis of ACh [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Preoperative statin therapy was not associated with a significantly different time to reach the peak during iontophoresis of ACh. This result is consistent with previous studies that found neutral or detrimental effects of statins in cardiac surgery particularly about the kidney outcomes [ 36 ]. In the same way, despite the detrimental effect of atrial fibrillation, a chronic beta-blocker therapy was not associated with a decrease in organ dysfunction or a shorter time to reach the peak during iontophoresis of ACh [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Statins had a protective effect against myocardial infarction in patients with non-cardiac procedures (2.3% in the statin group vs. 5.1% in the control group; OR, 0.44; CI 95%, 0.30-0.64), with a number needed to treat of 35. However, there was no effect on mortality, myocardial infarction or embolic episodes in the group of cardiac intervention 44 . The authors suggest that statin consumption is considered part of AFACS prophylactic treatment in case of contraindication for treatments of greater effectiveness, especially in coronary artery bypass graft and aortic valve replacement procedures.…”
Section: Statinsmentioning
confidence: 77%
“…Results from a meta-analysis of prospective observational studies provided conflicting evidence 23 . A comparison of studies is complicated by varying outcome definitions, types of surgery, and preoperative versus perioperative statin use.…”
Section: Discussionmentioning
confidence: 99%